Peningkatan Kapasitas SDM Koperasi Pondok Pesantren di Kabupaten Padang Lawas Provinsi Sumatera Utara - Fahmi, Indra (E-Coops-Day, 2025)
Islamic boarding school (Ponpes) is one of the oldest Islamic educational institutions in Indonesia. Its existence and role in shaping national life is recognized by society. In its development, Islamic boarding schools function as centers for guidance and teaching of Islamic religious knowledge (tafakh fi al-din) and have produced many ulama, community leaders and preachers. In line with the pace and demands of the times as well as developments in science and technology, Islamic boarding schools have carried out various innovations to strengthen their role while increasing the potential for environmental benefits. One form of real adaptation that has been implemented is the establishment of cooperatives in Islamic boarding school environments, known as Islamic boarding school cooperatives (Kopontren). The most important aspect of this service is not the placement of human resources, but the organization and mobilization of human resources so that Islamic boarding schools are able to manage their cooperatives independently and sustainably. The results of human resource development activities for Islamic boarding school cooperative managers show that the potential for human resources in Islamic boarding schools exists and can be developed further. Here we see that cooperatives play a big role in meeting the needs of the students and the community around the Islamic boarding school. Increasing the human resource capacity of cooperative administrators also aims to increase the understanding of Islamic boarding school cooperative administrators regarding cooperatives, the preparation of Bylaws (ART), Standard Operating Procedures (SOP) and Operational Management Systems (SOM). The target of this training is to increase the human resource capacity of Islamic boarding school managers, especially in cooperatives and the management's understanding of preparing Bylaws (ART), Standard Operating Procedures (SOP) and Operational Management Systems (SOM).